Achieving polydispersive HDPE by N, N, N-Co precatalysts appended with N-2, 4-bis(di(4-methoxyphenyl)methyl)-6-methylphenyl. Issue 71 (10th December 2020) - Yuan, Shi-Fang; Fan, Zhe; Yan, Yi; Ma, Yanping; Han, Mingyang; Liang, Tongling; Sun, Wen-Hua
Abstract : Introducing a practical application of N, N, N -Co precatalysts for highly linear polyethylenes with wide polydispersity and high molecular weights, targeting HDPE using Phillips catalyst. Abstract : A family of unsymmetrical 2-(2, 4-bis(di(4-methoxyphenyl)methyl)-6-MeC6 H2 N)-6-(1-(arylimino)ethyl)pyridine-cobalt dichloride complexes has been synthesized and characterized by NMR spectroscopy, FT-IR spectroscopy and elemental analysis as well as single crystal X-ray diffraction for Co2 and Co4 . Activated with either MAO or MMAO, all the cobalt precatalysts displayed high activities toward ethylene polymerization and produced highly linear polyethylenes with high molecular weights as well as wide polydispersities; for example, the performance using Co1 /MAO at 50 °C reached 9.17 × 10 6 g PE (mol of Co) −1 h −1 with the production polyethylene of molecular weight as high as M w = 3.14 × 10 5 g mol −1, T m = 134.3 °C besides its wide polydispersity of M w / M n of 54.6. Besides the terminal vinyl group of the resultant polyethylenes, it is rare for a late-transition metal catalyst to achieve highly linear polyethylenes with not only wide polydispersity but also high molecular weights, being similar to high-density polyethylenes produced using Phillips catalyst.